A CASE REPORT: SUSPECT PSYCHOGENIC ALOPECIA WITH SECONDARY DERMATITIS IN A PERSIAN CAT - Ailsa Cinta Lufiara; Putu Devi Jayanti; I Putu Gede Yudhi Arjentinia (Buletin Veteriner Udayana, 2026)
Psychogenic alopecia is hair loss caused by behavioral disorders that lead cats to groom excessively, resulting in skin lesions. Compulsive grooming causes alopecia, erythema, and secondary skin lesions. This case report discusses a Persian cat with complaints of alopecia, redness, and crusting without any infectious agents being found. Physical examination revealed self-induced alopecia, with pre-existing conditions within normal limits and a body condition score (BCS) of 5/9. Overall, the cat exhibited a docile temperament and normal activity levels. Complete blood count results were within normal ranges. The cat showed significant improvement after antihistamine therapy, a special diet for skin and hair, and grooming with hypoallergenic shampoo in a low-stress environment. However, relapse occurred after returning home to an environment with a high cat population. The cat recovered again after the owner provided more attention by regularly interacting and playing with it. Based on the history, examination findings, and therapeutic response, the diagnosis was established as suspected psychogenic alopecia with secondary dermatitis triggered by environmental stress.